Melatonin Elicitation Differentially Enhances Flavanone and Its Endogenous Content in Lemon Tissues Through Preharvest and Postharvest Applications - Vicente Agulló; María Emma García-Pastor; Daniel Valero (Agronomy)
The growing prevalence of metabolic diseases underscores the necessity for enhancing the nutritional value of widely consumed foods. The present study investigated the impact of melatonin elicitation on the accumulation of flavanones and endogenous melatonin in lemons. Preharvest treatments of 0.1 and 1 mM were applied, followed by postharvest treatment of 1 mM, either individually or in combination, and then cold storage. The quantification of bioactive compounds was conducted in various plant components, namely juice, albedo, flavedo, and leaves, employing HPLC-DAD and HPLC-MS/MS methodologies. Preharvest application of 1 mM melatonin resulted in a 26% increase in flavanone concentration in juice at harvest, while postharvest treatment induced a 19% increase during storage. The combination of both treatments resulted in elevated levels of flavanone (a 27% increase). With regard to melatonin levels, the combined treatments resulted in a significant increase in all tissues; however, the postharvest application alone achieved the highest concentration (6.99 µg L−1), particularly in the juice. The results of this study demonstrate the efficacy of melatonin elicitation, particularly in postharvest treatments, as a practical strategy to enhance the functional quality of lemons. This approach has the potential to facilitate the development of health-promoting foods and the valorisation of citrus byproducts. Further research is required to elucidate the role of melatonin in modulating the bioavailability and health effects of lemon phytochemicals in humans.